Analysis of Social Media Marketing Activities in the Influence of the Level of Consumer Trust in MSME Enterprises in Surakarta (Case Study on Vendorpanggung.id) - Achmad Baihaqi; Ihwan Susila (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This research aims to identify social media activities carried out to increase trust and gain consumer potential. Analyze the impact of social media activities on potential consumers' trust in MSME businesses and investigate the right social media approach model to gain the trust of potential consumers. The research method used is a qualitative method. The data source in this research comes from primary data. The primary data used in this research is the result of participatory observation carried out when visiting the Vendorpanggung.id office. Data collection methods use interview and observation techniques. Data Analysis Methods include transcribing all interviews and observation notes. Presentation of data in narrative form supported by direct quotations from interviews and observations. The results of this research show that the right approach in managing social media plays a very important role in building consumer trust in prospective MSME businesses. One of the key strategies found is presenting quality content. Compelling visual content, accompanied by a narrative that connects customers to the brand, can increase appeal and create trust. This shows that the display and representation of information has a significant impact on consumer perceptions.